Cultural Context and Multimodal Knowledge Representation: Seeing the Forest for the Trees - Cabezas-García, Melania; Reimerink, Arianne (Frontiers in Psychology, 2022)
Context, especially cultural context, has long been neglected in Terminology. Even though recent approaches (Diki Kidiri 2008; León-Araúz and Faber 2014; Faber and León-Araúz 2014) have acknowledged the relevance of culture in specialized communication, the development of culture in Terminology is still marginal. Culture is also underrepresented in terminological resources, which may respond to the complexity of reflecting the cultural component in the description of terms and concepts. However, conceptualization is dynamic and changes from culture to culture and, for that reason, an in-depth study on how the nature of human perception and cultural cognition influences the representation of concept systems and terms in specialized knowledge contexts is needed. Furthermore, to facilitate knowledge acquisition, contextual and conceptual information should go together with multimodal information, as the combination of textual and visual material improves understanding. This study integrates different types of context (i.e. semantic relations, frames, and culture) to describe a methodology for the selection and representation of multimodal information for culturally-bound concepts such as FOREST in terminological knowledge bases, based on the theoretical premises of Frame-Based Terminology. Different ideas of forest in European countries were analyzed and represented by means of culturally-adapted images, which are best suited to disseminate knowledge and foreground the role of culture in specialized communication.